GOVERNMENT DEBTS AND ECONOMIC GROWTH NEXUS: EMPIRICAL EVIDENCE FROM EMERGING ECONOMY - Emmanuel Imuede OYASOR (International Journal of Social and Educational Innovation)
The intricate relationship between government public debt and economic growth has long been a subject of scholarly inquiry, and its relevance is particularly pronounced in the context of emerging economies like Nigeria. The study examined the effect of Government public debt on economic growth; an empirical analysis from Nigeria. A yearly time-series data was adopted for this study from 2001 to 2022 was sourced from Central Bank of Nigeria (CBN), and Securities Exchange Commission (SEC). Data was subjected to linear regression analysis which was used to estimate the parameters of the model. The findings revealed that the coefficient for external debts services (GFD) is -0.256090, indicating a negative relationship with economic growth. This suggests that an increase in GFD leads to a reduction in economic growth. Cost of servicing the debt (CSD) has a coefficient of 0.429029, which also shows a negative relationship with economic growth. This implies that higher costs associated with servicing debt correspond to lower economic growth, and Government Domestic debts (GDD) have a coefficient of -0.263782, signifying a negative impact on economic growth. The study therefore recommended that the government should develop strategies to manage and stabilize foreign debt levels. This could involve negotiating favorable terms with international creditors, seeking concessional loans, and improving debt repayment schedules to prevent excessive debt accumulation and reduce the burden on the economy, implement policies aimed at reducing debt servicing costs. This could include refinancing existing high-cost debt with lower-interest options, optimizing the debt maturity structure, and improving credit ratings through sound fiscal policies and economic reforms, regulate the issuance and management of domestic debt to ensure it is used efficiently and does not crowd out private sector investment, also, ensure that both foreign and domestic debt are allocated to projects and sectors with high growth potential, and establish mechanisms for regular monitoring and evaluation of public debt levels and their impact on economic growth.